Environmental Drivers on Green Supply Chain Practices - V, Padmalalitha T; Rajeswari, TR (International Research Journal of Business Studies, 2020)
Environmental concern is one of the linchpins of business anxieties since post-industrial era in India. In the current scenario where the corporates in India are committing to green supply chain practices, this paper attempts to understand the key environmental drivers that impact green supply chain practices. Thus, the focus of this research paper is to recognize the direct and indirect effects of environmental drivers on the green supply chain practices. Quantitative data regarding corporate environmental drivers and green supply chain practices were collected from 12 manufacturing companies in India. Path analysis was performed through structural equation modeling technique to identify the significant environmental drivers. Further, the direct and indirect effects of the environmental drivers were determined by decomposing the structural equations. The results obtained demonstrated that regulatory pressure, customer pressure, socio-cultural pressure and competitor pressure affect green supply chain practices at varying levels of significance at different stages of the supply chain process. The result of this study invites necessary attention of the managers to undertake an analysis of the effect of potential environmental drivers on the functioning of green supply chain practices in their firms.